Misconceptions Reduction of Science High School Students on Buffer through Remedial Using Conceptual Change - Anna Kurnia; Tri Santoso; Ijirana Ijirana; Sri Mulyani; Kasmudin Mustapa (Universitas Tadulako, 2021)
This study aimed to analyze the results of the reduction of misconceptions among SMA Negeri 5 Palu students on the buffer material using the conceptual change learning strategy. This research is a type of pre-experimental research with a research design that is One group pretest-posttest design. This study contained one experimental group, namely students whose learning outcomes did not reach the minimum completeness criteria (MCC), then given a pre-test to determine the initial state of the experimental group, then given treatment, and given a post-test. Testing student misconceptions data using CRI. The results showed that the average percentage of students, who knew the concept (KC), did not know the concept (DKC), and misconceptions (MC) before the application of conceptual change learning strategies were 38.1%, 45.2%, and 16, respectively. 6% and the percentage of students knowing the concept (TC), not knowing the concept (NKC), and misconception (MC) after the application conceptual change learning strategies respectively 87.4%, 12.6%, and 0%. In conclusion, the average percentage reduction in misconceptions of grade XI IPA SMA Negeri 5 Palu on the buffer through remedial using the conceptual change learning strategy was 16.6%